Effectiveness Analysis Of Community Development Programs As A Form Of Social Mitigation Tools To Reduce Social Conflicts - Asmara, Febrian Dama; Rudito, Bambang (The Indonesian Journal of Business Administration, 2014)
Abstract. The interaction that occurs between oil and gas companies and local communities are closely related to the conflict. Conflicts often disturb the oil and gas company’s operations. Disturbances caused by conflict are not only affected the company but also will have an impact on the declining of state revenues due to the stop of production. As the second largest state revenue contribution after tax, the things that can disturb the operation of the upstream oil and gas will certainly affect the stability of the state economy. In order minimize those problems, mainly the social resistance which can lead to conflicts between the companies and the local communities, oil and gas companies implement the Community Development (CD) programs to mitigate social conflicts. This CD program is expected to effectively resolve social conflicts between companies and local communities in order to facilitate the upstream oil and gas operations. But it is necessary to study further to evaluate the relation between SR programs through the CD programs with social conflict mitigation. Therefore, by doing research on two (2) Production Sharing Contract Contractors (PSC Contractors) which are Medco E&P Rimau Asset and Joint Operating Body (JOB) Pertamina - Medco Tomori Sulawesi, this final project is expected to provide a comprehensive evaluation on the relation of SR programs through the CD programs with social conflict mitigation. The solutions from this final project are expected to give ideas on how the PSC Contractors should pay more attention to the implementation of CD programs as a form of social conflict mitigation. The results showed that the CD programs have relations with social conflicts mitigation, the role of the CD programs in social conflict mitigation is very important, and CD programs’ improvement effort to mitigate social conflicts is very high. However, CD programs implementation must have to follow the rules and norms. The control as well as the evaluation from the SKK Migas and PSC Contractors must be carried out to avoid the ineffective CD programs implementation which could leads into the failure of reaching the objectives. Recommendations from this final project are the adjustment of the CD programs implementation business process with the guidelines of ISO 26000: Guidance on Social Responsibility and implement the award ceremony as well as the appreciation of the Government of the Republic of Indonesia to companies from various industry sectors in the community development efforts. For internal PSC Contractors, the recommendations given are to implement systematic and continuous programs and education and provide training on related ISO 26000: Guidance on Social Responsibility to internal PSC Contractors. Keywords: ISO 26000: Guidance on Social Responsibility, Community Empowerment, Conflict